Quem vê close não vê corre: um estudo acerca das perspectivas de atuação do relações públicas empreendedor em eventos na cidade de Manaus - Ramos, Albérley César de Souza (Brasil, 2024)
Since 2014, when completed 100 years of existence, the Public Relations profession can begin to be recognized as essential for organizations in general and as an interesting path for opportunities in the entrepreneurship area, more specifically in the events area. It is clear that Public Relations professionals are striving to open their own businesses, such as communication agencies, digital marketing, event management and ceremonies, media consulting and strategic communication. In fact, it is based on the hypothesis that the possibilities of action for this professional have been so diversified that they even need to be cataloged to have a real notion and perception of the entire context, especially in the city of Manaus. The main objective of this research is to reflect and ponder about the possibilities and challenges for entrepreneurial performance in events by the Public Relations professional in Manaus. To achieve this objective, this work used a qualitative analysis of the data, which were obtained through the structured interview instrument, applied to three Public Relations professionals who decided to create and manage their own business in the events area in Manaus city. The results show that there is a desire to promote Amazonas' name to the rest of the world, in addition to the desire to satisfy customer needs. However, there is still a lack of incentives for the expansion of the sector, as well as for the improvement of professionals in the area. It is also possible to understand that the events area has been growing and bringing help from new technologies, in addition to the emergence of smaller and more select events.